The Protection and Preservation of Underwater Cultural Heritage: The Practice of Indonesia - Puspitawati, Dhiana; Wardana, Rangga Vandy (UI Scholars Hub, 2023)
The United Nations Convention on the Law of the Sea (UNCLOS) recognizes the protection and preservation of underwater cultural heritage found at sea by emphasizing preferential rights of the State of country of origin, the State of cultural origin, or the State of historical and archaeological origin. To preserve the rights of such States, the UNCLOS implicitly allows the removal of underwater cultural heritage upon prior approval from coastal States based on the State’s cooperation. On the other hand, the Convention for the Protection of the Underwater Cultural Heritage 2001 (2001 UCH Convention) strictly prohibits any exploitation and commercialization of such cultural heritage and applies the in-situ preservation for underwater cultural heritage. This article aims to discuss the practice of Indonesia in regulating underwater cultural heritage found in Indonesian waters. This research found that Indonesia’s law allows the removal of underwater cultural heritage and made commercial salvage for underwater cultural heritage legal. In addition to this, with the enaction of the current Job Creation Law 2021, underwater cultural heritage is listed as one of the fields in which open-investment is applied. While Indonesia has national laws relating to cultural heritage, provisions on underwater cultural heritage is lacking. This article proposes a model that can be adopted by Indonesia in protecting and preserving underwater cultural heritage. It is argued that although Indonesia is not a party to UCH Convention 2001, it is a party to the UNCLOS and is binded to the provisions envisaged in it, which is to protect and preserve underwater cultural heritage.